An exploration of the relationships between posttraumatic growth, sense of coherence and meaningfulness, in the South African context. - Walsh, Samantha (My University, 2012)
The objective of this study is to undertake research regarding Posttraumatic Growth and its relationship with Sense of Coherence, within the South African context. In addition, the associations between the three domains of SOC, in particular Meaningfulness, and the five domains of PTG, will be investigated. A further aim of this study is to explore whether the relationship between posttraumatic stress symptoms and Posttraumatic Growth is moderated by Meaningfulness. Sample: The sample consisted of tertiary education students, 18 years and older, and who have experienced a traumatic event as defined by the Traumatic Stress Schedule (N=79). Measures: In addition to a demographic questionnaire, the following measures were administered: the Sense of Coherence Scale (SOC), the Posttraumatic Growth Inventory (PTGI), the Impact of Event Scale - Revised (IES-R), and the Traumatic Stress Schedule (TSS). Results: Participants reported moderate scores on overall PTG with lower SOC scores relative to similar samples in the literature. Age was found to be associated with PTG, and PTG was associated with subjective distress as measured by the IES-R. In addition, those reporting PTG, particularly in the areas of Relating to Others, New Possibilities and Appreciation of Life, evidenced lower levels of Comprehensibility, and those low on Comprehensibility tended to report higher levels of subjective distress. High levels of subjective distress also appeared to be associated with lower levels of Manageability. Findings further suggested that participants who had been exposed to multiple traumas, as well as those who reported higher subjective distress, generally evidenced lower SOC. Multiple trauma exposures were strongly associated with increased subjective distress. Implications of the findings and recommendations for future research are discussed.
Keywords: Posttraumatic growth; Sense of Coherence; Meaningfulness; Comprehensibility; Posttraumatic stress symptoms; Multiple traumas